Climate–agriculture–gender inequality hotspots: Insights for Nigeria - Azzarri, Carlo; Bamiwuye, Temilolu; Kedir Jemal, Mekamu (International Food Policy Research Institute, 2025)
Climate change intensifies risks in Nigeria’s agri-food systems, disproportionately affecting women due to social inequalities that increase their vulnerability and limit their adaptive capacity. Hotspot areas are concentrated in northern and north-central Nigeria, notably Bauchi, Benue, Kano, Jigawa, Kebby, Nasarawa, Niger, Sokoto, and Zamfara. Policy actions should prioritize climate-smart agriculture, gender-sensitive climate services, and social protection to improve resilience and equity.